The Role of Oxidative-Antioxidative Stress and Uromodulin Indicators and Polymorphism of Its Genes in the Development of Cardiorenal Syndrome - Khalilova Feruza Abdujalolovna (American Journal of Biomedicine and Pharmacy, 2025)
Cardiorenal syndrome (CRS) associated with chronic heart failure (CHF) is characterized by simultaneous impairment of cardiac and renal function, leading to increased complications and decreased quality of life in patients. Oxidative stress is an imbalance in the antioxidant system, associated with inflammatory processes, including malondialdehyde (MDA), superoxide dismutase (SOD), and α-tumor necrosis factor (α-TNF), which aggravates the course of CRS. In particular, the effect of uromodulin indicators and polymorphism of its genes on these processes is one of the important areas that are not well covered from a scientific and practical point of view. Uromodulin (Tamm-Horsfall protein) is an important glycoprotein in the kidney, and its secretion and genetic characteristics can directly affect kidney function, inflammation, and oxidative stress processes. Therefore, the study of uromodulin indicators and its gene polymorphisms in the development of CRS is undoubtedly important for the diagnosis of CRS, individualization of treatment and improvement of nutritional status.